A scoping review of qualitative research on perceptions of one's own alcohol use. (23rd November 2020) - Morris, Stephanie; Stewart, Duncan; Madden, Mary; McCambridge, Jim
Abstract: Background: This scoping review aims to map the extent, range and nature of qualitative research on people's 'perceptions' of their own alcohol consumption. Methods: A systematic search of five electronic databases was conducted. A total of 915 abstracts were screened and 452 full texts examined, of which 313 papers met the inclusion criteria (including a report of qualitative data on perceptions, experiences or views of people's own drinking in peer-reviewed journals published in English). Results: This study maps the available literature assembled over approximately 30 years, which was found to be extensive and diverse. Many existing studies are focused largely on people's 'experiences' of their own drinking behaviours, particularly when they were drinking in ways commonly understood as heavy, risky or problematic. Fewer studies focused on populations whose drinking was not heavy or was risky in less obvious ways, such as older adults prescribed medications for chronic health conditions. Most studies were conducted since 2010, with the rate of publications increasing since 2014. Conclusions: This review identifies gaps in the evidence regarding people's perceptions of their own drinking and opportunities for qualitative studies to make valuable contributions to alcohol research. Gaps discussed include patterns of drinking that are less obviously problematic, and in relation to consumption of alcohol in those parts of the world where overall consumption and harms from alcohol are high. Such studies could usefully be informed by existing studies in the evidence mapping.